Analysis of the physcial properties of particleboard from a mixture of cocoa pod peel powder and styrofoam - ety jumiati; endang sagita ritonga; Abdul halim daulay (Universitas Islam Negeri Sumatera Utara Medan, 2021)
AbstractAbstract. This study aims to determine the effect of optimal physical properties and microstructure on particleboard samples. The percentage variations of cocoa pod peel powder mixture, styrofoam with epoxy resin adhesive were sample A (69:0:30), sample B (68:2:30), sample C (67:3:30), and sample D (66:4:30). 6:30). The materials were compressed were a hot press and a conditioning time of 14 days. sThe most optimum particleboard sample was found in sample B with values of density, moisture content, and thickness expansion, respectively 0,80 g/cm2, 7,74%, and 9,32%, and met the standards of SNI 03-2105- 2006. The surface shape of the particle board morphology in sample B shows the composition of the material with the adhesive binding optimally so that there are very few empty spaces or cavities. Keywords: cocoa pod husk powder, styrofoam, particle board, epoxy resin.